Safety evaluation of a lyophilized platelet‐derived hemostatic product. Issue 12 (18th November 2018) - Barroso, Jeffrey; Osborne, Barbara; Teramura, Gayle; Pellham, Esther; Fitzpatrick, Michael; Biehl, Ruth; Yu, Anna; Pehta, Joan; Slichter, Sherrill J.
Abstract : BACKGROUND: Hemorrhage causes significant morbidity and mortality in people aged <65 years. A lyophilized platelet‐derived hemostatic agent (Thrombosomes) demonstrated hemostatic efficacy in animal models. We report the results of the first safety trial of autologous Thrombosomes given to normal subjects. STUDY DESIGN AND METHODS: Ten subjects received autologous Thrombosomes prepared from their apheresis platelets, and five control subjects received a buffer solution. There were five cohorts, with three subjects per cohort (two in the Thrombosomes group and one in the control group). Doses escalated from 1/1, 000 to 1/10 of a proposed efficacious dose. Cohorts 4 and 5 received the highest dose, but in Cohort 5, one‐half the dose was infused 2 hours apart. Cohorts 1 through 3 were monitored for 42 days, Cohorts 4 and 5 were monitored for 60 days using hematology, coagulation, and chemistry assays and antibody testing. RESULTS: There were no serious adverse events (AEs) and no subject withdrawals. There were eight treatment‐related AEs (TRAEs) in 5 of 15 subjects (33%) (four in the Thrombosomes group and one in the control group). Of four subjects receiving the highest doses, three had TRAEs. One had elevated D‐dimer, prothrombin fragment 1 + 2, and white blood cell count (subject had concurrent upper respiratory tract infection); one had T‐wave inversions in precordial leads V2 and V3 without elevated troponin or symptoms; and one had a platelet autoantibody without change in platelet count. All subjects' TRAEs resolved by Day 21. CONCLUSION: There were no serious AEs in this small study. Thrombosomes were considered safe at the doses assessed. Future, larger trials will be needed to further assess safety and efficacy.